2012
DOI: 10.1007/s00339-012-6897-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrical responses and dielectric relaxations in giant permittivity NaCu3Ti3TaO12 ceramics

Abstract: Dielectric relaxations and electrical responses in NaCu 3 Ti 3 TaO 12 ceramics were investigated as a function of temperature. NaCu 3 Ti 3 TaO 12 ceramics exhibit giant dielectric constants with values of ε ∼ 1.45-2.08 × 10 4 . Two sets of thermally activated dielectric relaxations were observed in low and high temperature ranges. Sintering conditions have an insignificant influence on the microstructure of NaCu 3 Ti 3 TaO 12 ceramics, and have a slight impact on their ε values. Thermally activated electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…Therefore, it can be concluded that the low‐temperature dielectric relaxation is attributed to the grain‐boundary effect. The disappearance of high‐temperature dielectric loss hump might be due to higher conductivity at high temperature and the expected relaxation peak may be concealed by high conductivity . To further verify this deduction on solid ground, the ac conductivity σ′ data have been collected to obtain comprehensive electric details.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, it can be concluded that the low‐temperature dielectric relaxation is attributed to the grain‐boundary effect. The disappearance of high‐temperature dielectric loss hump might be due to higher conductivity at high temperature and the expected relaxation peak may be concealed by high conductivity . To further verify this deduction on solid ground, the ac conductivity σ′ data have been collected to obtain comprehensive electric details.…”
Section: Resultsmentioning
confidence: 98%
“…无 机 材 料 学 报 第 32 卷 介电材料被广泛地应用于制造电容器、存储器 和滤波器等电子元件, 随着集成电子技术的发展, 高介电材料变得日益重要。近年来, 研究者相继开 发了一些具有高介电常数的类钙钛矿氧化物材料, 钛酸铜钙(CaCu 3 Ti 4 O 12 , CCTO)是其中最具有代表性 的材料 [1][2][3][4][5][6] , 它室温的相对介电常数高达 10 4 数量级, 并且介电常数几乎不随频率和温度发生变化 [1][2][3][4] 。为 了探索 CCTO 的高介电性质起源, 研究者对 CCTO 的相关电学性质进行了详细研究, 发现 CCTO 的电 学分布是不均匀的, 由绝缘性的晶界和半导性的晶 粒组成, 所以内阻挡层电容效应引起了 CCTO 的高 介电性 [4,[7][8][9] 。在这种解释机制中, CuO 第二相、氧缺 陷和 Ti 与 Cu 离子的变价对于形成绝缘性的晶界和 半导性的晶粒起了至关重要的作用 [4,[7][8][9] 。从内阻挡 层电容效应的机制解释出发, 高介电性质应该在化 学组分和晶体结构与 CCTO 很类似的氧化物中普遍 存在。最近, 研究者在多种 CCTO 类氧化物中发现 了高介电性质, 如 ACu 3 Ti 4 O 12 (A = Sr [10] 、Cd [11] 、 Y 2/3 [12] 、 La 2/3 [10,13] 、 Bi 2/3 [10,14] 、 Na 1/2 Y 1/2 [15] 、 Na 1/2 La 1/2 [16][17] 、Na 1/2 Sm 1/2 [18] 或 Na 1/2 Bi 1/2 [19][20][21] , 等) 和 NaCu 3 Ti 3 BO 12 (B = Sb [22] 、Nb [23] 或 Ta [24] )。 NaCu 3 Ti 3 BO 12 体系材料晶粒的半导性应该与 Cu、Ti、Sb、Nb 和 Ta 离子的变价有关 [22][23][24] [4,22,24,27] 。 图 3 不同温度烧结的 NCTSTO 陶瓷的室温介电频谱 Fig. 3 Room temperature dielectric dispersion spectra of the NCTSTO ceramics sintered at different temperatures 图 4 1060℃烧结的 NCTSTO 陶瓷在不同温度下的介电频谱...…”
unclassified
“…3 Room temperature dielectric dispersion spectra of the NCTSTO ceramics sintered at different temperatures 图 4 1060℃烧结的 NCTSTO 陶瓷在不同温度下的介电频谱 和特定频率下的介电温谱 Fig. 4 (a [4,22,24,27] [27] 。这里, 可以发现该等效电路也适用于描述 NCTSTO 陶瓷 的介电性质和复阻抗谱。从 NCTSTO 陶瓷的复阻抗 谱可以得到其室温、100、200 和 300℃的晶界电阻 率分别为 1.73×10 7 、 1.32×10 6 、 1. CuO 第二相导致了晶界绝缘 [7,[28][29] , 氧缺陷和 Ti、 Cu 离子的变价导致了晶粒的半导性 [28][29][30][31][32][33] 。对于 NCTSTO 陶瓷, 通过 XRD 直接检测到在某些烧结 条件下制备的陶瓷中含有 CuO 第二相。 为了得到晶 粒半导性的细节信息, 对 NCTSTO 陶瓷进行了 X 射 线光电子能谱(XPS)测试。图 6 给出了 1060℃烧结 的 NCTSTO 陶瓷的 Cu-2p、Ti-2p、Sb-3d 和 Ta-4f 的 XPS 图谱及其多峰拟合曲线, 采用 Gauss 多峰拟 合方法拟合, 因为 Sb-3d 5/2 峰和 O1s 峰相互重合, 所 以利用 Sb-3d 3/2 峰来分析 Sb 离子的价态。如图 6(a) 所示, Cu-2p 3/2 峰分解成结合能为 934.0 和 932.3 eV 的两个峰, 意味着 Cu-2p 3/2 峰可以分解为 Cu 2+ 和 Cu + 的贡献 [34][35] 。 同样的, 如图 6(b)、 (c)和(d)所示, Ti-2p 3/2 峰分解为 Ti 4+ (459.4 eV)和 Ti 3+ (458.8 eV)的贡献 [34][35] ; Sb-3d 3/2 峰分解为 Sb 5+ (540.8 eV)和 Sb 3+ (540.2 eV)的 贡献 [35] ; Ta-4f 5/2 峰分解为 Ta 5+ (26.5 eV)和 Ta 3+ (25.7 eV) 的贡献 [35] , 说明 NCTSTO 陶瓷中存在 Cu 2+ /Cu + 、 Ti 4+ /Ti 3+ 、Sb 5+ /Sb 3+ 和 Ta 5+ /Ta 3+ 的变价。…”
unclassified